Constraints on clumps in the representative wind of the WN8 Wolf–Rayet star HD 96548 = WR 40 with simultaneous broad-band light and linear-polarization variability. Issue 3 (22nd December 2022) - Ignace, R; Moffat, A F J; Robert, C; Drissen, L
ABSTRACT: We report precision ground-based broad-band optical intensity and linear-polarization light curves for the sky's brightest WN8 star, WR 40. WN8 stars are notorious for their high level of variability, stemming from stochastic clumps in their strong winds that are slower and less hot than the winds of most other Wolf–Rayet (WR) stars. We confirm previous results that many WR stars display an amplitude of variability that is an order of magnitude higher in photometry than in polarimetry. For the first time, the unique nature of near simultaneity of our photometric and polarimetric observations of WR 40 allows us to check whether the two types of variability show correlated behaviour, of which we find none. Assuming simple temporal functions for the brightness and polarization of individual clumps, a model for simulated light curves is found to reproduce the properties of the observations, specifically the absence of correlation between photometric and polarimetric variations, the ratio of standard deviations for photometric and polarimetric variability, and the ratio of the average intrinsic polarization relative to its standard deviation. Mapping the solution for time variability to a spatial coordinate suggests that the wind clumps of WR 40 are free-free emitting in addition to light scattering.